ESTRUS CYCLE OF Rattus norvegicus EXPOSED TO CIGARETTE SMOKE AFTER TREATMENT ETHANOL EXTRACT OF GRASS (Biophytum petersianum Klotzsch) - Simatauw, Anniestasya Z; Unitly, Adrien Jems Akiles (RUMPHIUS, 2019)
Kebar grass is a plant that contains phytoestrogens which have the same effect as endogenous estrogens which are thought to be able to increase endogenous estrogen levels in the blood due to the adverse effects of free radicals in the form of cigarette smoke. The purpose of this study was to determine the effect of the ethanol extract of kebar grass (Biophytum petersianum Klotzsch) on the length of the estrous cycle of Rattus norvegicus rats exposed to cigarette smoke. The research used an experimental method, namely a completely randomized design with four treatment groups and three replications. Rats the negative group was fed normally, the positive control group was exposed to cigarette smoke for 28 days, while the rats in the Kebar grass ethanol extract dosed group were given cigarette smoke exposure for 28 days, and were gived Kebar grass ethanol extract for 28 days. Vaginal smears were taken in the morning with a span of 24 hours for 28 days. Changes in the vaginal epithelium are examined to determine the phase of the estrous cycle using a microscope. The data obtained were analyzed by Analysis of Variance (ANOVA)-SPSS version 16.0 followed by Duncan test with a 95% confidence interval (α=0.05). The results showed that administration of Kebar grass ethanol extract was able to extend the estrous cycle time at a dose of 0.135 mg/head/day due to prolongation of the proestrus and estrus phases.